2015
DOI: 10.3390/e17031063
|View full text |Cite
|
Sign up to set email alerts
|

Fully Bayesian Experimental Design for Pharmacokinetic Studies

Abstract: Utility functions in Bayesian experimental design are usually based on the posterior distribution. When the posterior is found by simulation, it must be sampled from for each future dataset drawn from the prior predictive distribution. Many thousands of posterior distributions are often required. A popular technique in the Bayesian experimental design literature, which rapidly obtains samples from the posterior, is importance sampling, using the prior as the importance distribution. However, importance samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 42 publications
0
57
0
Order By: Relevance
“…The applied statistician's default approach to analysing data in a Bayesian framework is to use uninformative priors. When designing an experiment, it is reasonable to assume that, generally, there is historical and/or expert opinion available to formulate an informative prior (e.g., Clyde et al, 1996, Stroud et al, 2001, Ryan et al, 2015. Therefore, the prior predictive distribution gives ranges of data values that the experimenter believes to be plausible.…”
Section: Bayesian Optimal Design Theorymentioning
confidence: 98%
“…The applied statistician's default approach to analysing data in a Bayesian framework is to use uninformative priors. When designing an experiment, it is reasonable to assume that, generally, there is historical and/or expert opinion available to formulate an informative prior (e.g., Clyde et al, 1996, Stroud et al, 2001, Ryan et al, 2015. Therefore, the prior predictive distribution gives ranges of data values that the experimenter believes to be plausible.…”
Section: Bayesian Optimal Design Theorymentioning
confidence: 98%
“…Results obtained from a two compartment analysis of data from Ryan et al (2014) The prior predictive distribution of this two-compartment model is shown in Fig. 8.…”
Section: Example 2: Bayesian A-optimality For One and Two Compartmentmentioning
confidence: 99%
“…We propose to re-design this study to minimise the uncertainty about population PK parameters such that differences between PK profiles for ECMO versus non-ECMO sheep can be investigated. The general form of the models considered in Ryan et al (2014) and in this paper are as follows. Let the time of blood …”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations